The suitability of depression, anxiety and stress scale (DASS21-M) among smokers / Nur Amirah Fikriyah Mohd Suhaidi - Mohd Suhaidi, Nur Amirah Fikriyah (2020)
It is about 54% of adult males in Malaysia is a smoker. Thus, this population represent half of the Malaysian population. Having a validated questionnaire for this specific population is necessary to nurture a research path in that particular area. The Malay version of Depression, Anxiety and Stress Scale (DASS21-M) was widely used screening instruments in clinical setting. Perhaps, this instruments have been validated by others clinical population such as diabetics and Parkinson's disease. Thus, it is very important to identify the suitability of this instrument to the smoker's population. Objective: The aim of this study is to identify the suitability of depression, anxiety and stress scale (DASS21-M) among smoker's population. To determine the concurrent validity of DASS-M Method: This is cross sectional study administered among 120 smokers. The study instruments include Depression, Anxiety and Stress Scale (DASS21-M), Beck Depression Inventory (BDI-M), Beck Anxiety Inventory (BAI-M) and Profile of Mood States (POMs-M). A set of the questionnaire was administered by 120 daily smokers. The convenient sampling (26.92 ± 12.001) has been used for this study. The data has been analysed using IBM SPSS Statistics 23.0 and Spearman's' rho Correlation Test. Results: This Study shows present study shown significant correlation of Depression, Anxiety and Stress Scale (DASS21-M) with between Beck Depression Inventory (BDI-M), Beck Anxiety Inventory (BAI-M) and Profile of Mood States (POMs). Conclusion: There is significant correlations between Profile of Mood States (POMs), Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), and Depression, Anxiety, and Stress Scale (BM DASS21) among smoker's population.